Pengaruh PENGARUH NET PROFIT MARGIN DAN RETURN ASSETS TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI - Situmeang , Rodearni; Purba , Dianty Putri; Sihaloho, Riandini Carmelita (Jurnal Ekonomi Bisnis Digital, 2023)
Profit growth is the difference between existing profits from the current year and profits in the previous year. The purpose of this study is to obtain information about the effect of net profit margin and return on assets on growth profits. The companies that were included in the current population interview were the food and beverage industry on the IDX. Purposive sampling was used for samples from around 18 different businesses. Based on the results of the study, it was concluded that the net profit margin of the food and beverage industry is relatively good, but the return on investment from asset investment is not so profitable.